2018
DOI: 10.1093/pcp/pcy091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Alternative Splicing Profiles of the Lipoxygenase Gene Family in Tea Plant (Camellia sinensis)

Abstract: Oxylipins, including jasmonic acid (JA) and volatiles, are important for signaling in plants, and these are formed by the lipoxygenase (LOX) enzyme family. There is a large gap in understanding of the underlying molecular basis of their roles in tea plants. Here, we identified 11 CsLOX genes from the tea plant (Camellia sinensis), and characterized their phylogeny, gene structure and protein features into three subclasses. We then examined their enzymatic activities, LOX expression and alternative splicing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 87 publications
6
79
1
6
Order By: Relevance
“…Four of these regulatory relationships were positive, whereas the other three were negative. Recent studies confirmed that JA/MeJA biosynthesis involves a series of genes, including LOX, AOS, AOC, OPR, ACX, and MFP2 (Wasternack and Feussner, 2018;Zhu et al, 2018). Among these genes, LOX mediates the first step of JA/MeJA biosynthesis.…”
Section: High Jasmonic Acid and Methyl Jasmonate Contents And An Endomentioning
confidence: 93%
“…Four of these regulatory relationships were positive, whereas the other three were negative. Recent studies confirmed that JA/MeJA biosynthesis involves a series of genes, including LOX, AOS, AOC, OPR, ACX, and MFP2 (Wasternack and Feussner, 2018;Zhu et al, 2018). Among these genes, LOX mediates the first step of JA/MeJA biosynthesis.…”
Section: High Jasmonic Acid and Methyl Jasmonate Contents And An Endomentioning
confidence: 93%
“…In our previous study, we found that some AS events were tissue specific in stem and root; we also found that some AS isoforms were the major transcripts involved in the flavonoid synthesis pathway, which suggested AS is positively correlated with the contents of catechins [29]. We also reported that six CsLOXs (lipoxygenase) varied significantly in relative abundances under the different stresses [30]. However, these studies on AS emphasize largely on secondary metabolism.…”
Section: Introductionmentioning
confidence: 95%
“…These results were consistent with those of previous reports in other plant species [31]. During the sharp cooling treatment of tea plants, the numbers of AS events under low-temperatures [cold acclimation of 6 h at 10°C, day/night temperature (CS), cold acclimation of 7 days at 10/4°C, day/night temperature (CA1) and cold acclimation of 7 days at 4/0°C, day/ night temperature (CA2)] were significantly increased relative to AS events in those growing under normal temperature (NA, 25/20°C, day/night temperature); thus, the amount of CS (30,212), CA1 (30,325) and CA2 (30,552) was about 3000 more than NA (27,234), respectively. It is noteworthy that the number of AS events (24,616) tremendously decreased under temperature recovery condition compared with both CA treatment and NA groups, implying that many AS genes had adapted to low-temperature environment and resulted in reduced occurrence of AS events during DA (de-acclimation) of tea plant.…”
Section: Global Identification and Classification Of As Eventsmentioning
confidence: 99%
“…To deal with various threats, plants can activate defense mechanisms only when necessary. Such inducible defenses are triggered by wounding and insect attacks through jasmonate (JA) signaling (Mewis et al 2005; Escobar-Bravo et al 2017; Tsuda 2017; Zhu et al 2018; Zhou et al 2018; Nakano et al 2018), while constitutive defenses are continuously expressed.…”
Section: Introductionmentioning
confidence: 99%